2020
DOI: 10.34069/ai/2020.28.04.59
|View full text |Cite
|
Sign up to set email alerts
|

The Translation Peculiarities of the Ancient Ukrainian Monument «On the Campaign of Igor» by American Researchers Jack Haney and Eric Dahl

Abstract: The article analyzes some peculiar features in the English translation of the glorious Ukrainian literary monument «On the Campaign of Igor» («Slovo o polku Igoreve») by the famous American researches Jack Haney and Eric Dahl. It also considers the various publications and translations of the work in English, taking into account the Ukrainian monument translation. It is stated that in America there are very few works published by the scholars on this issue. It is connected not with the lack of interest in «On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Wongsa and Son (2022) found that when used as a delivery and communication tool, Facebook could create an interactive and flexible learning environment for EFL learners, enabling them to actively communicate and collaborate with their teachers and peers in drama-based English activities. Similarly, Kostikova et al (2019) found that Facebook was effective in improving English-speaking skills for upper-intermediate learners aiming to pass the First Certificate in English exam. In brief, although various social media platforms have shown varying effects on the outcomes of English-language learning, they have been recognized and widely utilized to improve the Englishspeaking skills of learners of all ages.…”
Section: Social Media-based Learning For English Acquisition and Spea...mentioning
confidence: 90%
“…Wongsa and Son (2022) found that when used as a delivery and communication tool, Facebook could create an interactive and flexible learning environment for EFL learners, enabling them to actively communicate and collaborate with their teachers and peers in drama-based English activities. Similarly, Kostikova et al (2019) found that Facebook was effective in improving English-speaking skills for upper-intermediate learners aiming to pass the First Certificate in English exam. In brief, although various social media platforms have shown varying effects on the outcomes of English-language learning, they have been recognized and widely utilized to improve the Englishspeaking skills of learners of all ages.…”
Section: Social Media-based Learning For English Acquisition and Spea...mentioning
confidence: 90%
“…Kostikova et al (2019) conducted a study in Ukraine to determine if Facebook could be used as an extra tool to teach speaking skills for the FCE test. Twenty-four Kharkiv nonlinguistic university students participated in this mixed methods research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature contains studies demonstrating the convenience of using SNS to share educational resources, increase student/teacher engagement and improve students’ specific skills (Cavus et al, 2021; Estrella, 2018; Koranteng et al, 2018; Norhailawati et al, 2019; Pérez-López et al, 2020; Saienko et al, 2020; Solmaz, 2019). Nonetheless, the body of knowledge has also drafted the disadvantages of using SNS in education.…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts related to this issue span various domains, encompassing the linguistic and didactic aspects of the effectiveness and practical relevance of studying social sciences and humanities (Kostikova et al 2019). Additionally, investigations explore the role of the humanitarian component in fostering the development of civic engagement among future professionals, emphasizing the importance of critical thinking within the realm of professional communication (Cavus and Ibrahim 2017;Severino and Tavares 2020).…”
Section: Literature Reviewmentioning
confidence: 99%